2010
DOI: 10.1101/gad.583310
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-mediated mRNP dynamics and surveillance prior to budding yeast mRNA export

Abstract: The evolutionarily conserved mRNA export receptor Mex67/NXF1 associates with mRNAs through its adaptor, Yra1/REF, allowing mRNA ribonucleoprotein (mRNP) exit through nuclear pores. However, alternate adaptors should exist, since Yra1 is dispensable for mRNA export in Drosophila and Caenorhabditis elegans. Here we report that Mex67 interacts directly with Nab2, an essential shuttling mRNA-binding protein required for export. We further show that Yra1 enhances the interaction between Nab2 and Mex67, and becomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
183
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 144 publications
(190 citation statements)
references
References 52 publications
(84 reference statements)
7
183
0
Order By: Relevance
“…34,35). It seems likely that every maturation step is controlled, in this case the 3 0 -end processing step, and that the passage of each maturation 'checkpoint' might be labelled with the addition of one or more Mex67 molecules.…”
Section: Discussionmentioning
confidence: 99%
“…34,35). It seems likely that every maturation step is controlled, in this case the 3 0 -end processing step, and that the passage of each maturation 'checkpoint' might be labelled with the addition of one or more Mex67 molecules.…”
Section: Discussionmentioning
confidence: 99%
“…A relevant target of Tom1 appears to be Yra1, an adaptor protein linking mRNA to Mex67 (Iglesias et al 2010). Monoubiquitylation and K48-diubiquitylation of Yra1 do not induce proteolysis, but promote dissociation from the Mex67-mRNP complex, which facilitates mRNA export.…”
Section: Processing Of Mrnasmentioning
confidence: 99%
“…Indeed, previous studies (Duncan et al 2000;Neumann et al 2003;Rodriguez et al 2003;Gwizdek et al 2005;Iglesias et al 2010) have demonstrated the direct roles of two HECT domain-containing E3 ubiquitin ligases, namely Tom1 and Rsp5, in mRNA export in yeast. Recently, we have demonstrated that Mdm30, an F-box protein, is also involved in stimulation of nuclear export of mRNA in yeast Shukla et al 2009).…”
Section: Introductionmentioning
confidence: 99%